PERAN TEORI QIRA’AT DALAM MEMAHAMI AYAT RELASI GENDER - Ahmad Muttaqin (Muwazah, 2016)
Al-Quran at the first time was sent down to transform the bias gender relation. In relation to this, it is necessary to let the Quranic verses to talk about gender itself by using the variant readings (Qira’at) of the Al-Quran. This paper aims to built the argument how important the qira’at is to understand the verses talking about gender. For example, this will analyze the Q.S. Al-Nisa’ (4): 19. This concludes that variant readings (qira’at) contributes to understand the Quran thematically and contextually. Second, using the qira’at in Q.S. Al-Nisa’ (4): 19, we understand how to position the women more respectfullyAl-Quran pada saat pertama diturunkan untuk mengubah hubungan bias gender. Sehubungan dengan ini, perlu untuk membiarkan ayat-ayat Al-Quran berbicara tentang gender itu sendiri dengan menggunakan bacaan varian (Qira'at) dari Al-Quran. Paper ini bertujuan untuk membangun argumen tentang pentingnya Qira'at untuk memahami ayat-ayat Al-Quran berbicara tentang gender. Misalnya, analisis Q.S. Al-Nisa '(4): 19, dengan kesimpulan bahwa varian bacaan (Qira'at) memberikan kontribusi untuk memahami Quran tematis dan kontekstual dan menggunakan Qira'at dalam Q.S. Al-Nisa '(4): 19, bisa memahami posisi kaum perempuan dengan lebih terhormat.